Pengembangan Modul Ajar Matematika Berbasis Kearifan Lokal Anyaman Rajapolah pada Materi Persamaan Linear Satu Variabel untuk Peserta Didik SMP - Nurmaya, Rani; Prabawati, Mega Nur (Papanda, 2026)
Abstract mathematics learning often poses challenges for students in understanding concepts, particularly in the topic of Linear Equations in One Variable (LEOV). Integrating local wisdom into instructional materials is considered a relevant approach to addressing this issue. This study aims to develop a mathematics learning module based on the local wisdom of Rajapolah weaving in the context of LEOV, designed to support students’ conceptual understanding and to facilitate their ability to model real-life situations into linear equation forms. The research employed a research and development methodology using the ADDIE model, which includes the stages of analysis, design, development, implementation, and evaluation. The research instruments consisted of expert validation sheets as well as readability assessment questionnaires completed by teachers and students. Expert validation results indicated that the developed module was categorized as highly valid in terms of content feasibility, presentation, language, and cultural integration. Readability testing conducted with teachers and students also showed that the module was easy to understand, although several sentences required minor simplification. Overall, the module was deemed appropriate for use as a contextual learning resource that helps students construct a more meaningful understanding of LEOV while fostering appreciation of local culture. This study recommends the incorporation of local wisdom in the development of learning modules to strengthen the contextualization of mathematics instruction.